TRENDS OF THE DEVELOPMENT OF ENTERPRISES IN THE AGRARIAN SPHERE OF UKRAINE DURING THE WAR (Development Service Industry Management, 2023)
The article examines the issue of the development of agrarian enterprises and the possibility of resuming their activities after the impact of the actions of the aggressor country on the territory where they carried out their activities. It has been investigated that the effective functioning of the agricultural sector depends on a number of factors that arise depending on the possible occurrence of natural or industrial risks, which largely do not depend on farmers, but directly affect the results of agricultural enterprises. The main problems that affect the development of the agricultural industry during the war are identified, namely: the occupation of the territories of Ukraine, the destruction or damage of the agricultural machinery of farmers, insufficient fuel due to military operations in March - May 2022, the lack of highly qualified workers in the territories adjacent to the demarcation zone , difficulties in importing seeds in 2022, disruption of logistics routes to countries in Europe, the USA, Africa and India, to which the main export of products took place. The main Internet portals where the main damages suffered by natural and legal entities from the actions of the aggressor can be submitted are considered. A number of priorities for the development of agricultural business in different regions of Ukraine during the war and post-war periods have been formulated. The main measures for the successful implementation of priority tasks for the development of agricultural enterprises and farms are proposed: attraction of additional internal and external investments in the creation of new and development of existing productions of the processing link of agribusiness, development of new external logistics routes through the countries of the European Union for the export of agricultural products, activation of diplomatic negotiations to increase the quotas for the export of all groups of agricultural products to the markets of the European Union, the formation of a new favorable legislative framework for the implementation of investment projects in the field of renewable energy and other industries related to agriculture, lending for the construction of processing industry enterprises for the creation of added value and the transition from the country of the exporter of raw materials to the exporter of finished products to the countries of Europe and the USA.
Keywords: agricultural enterprises; agricultural machinery; investments; loans; grants; military operations